2020
DOI: 10.3389/fonc.2020.537051
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Selection and Survival Outcomes in Locally Advanced Proximal Gastric Cancer: A National Cancer Data Base Analysis

Abstract: Background: We aimed to assess long-term survival between locally advanced proximal gastric cancer (LAPGC) patients who underwent proximal gastrectomy (PG) and those who underwent total gastrectomy (TG) to evaluate the optimal extent of resection and adjuvant therapy. Materials and Methods: Patients diagnosed with locally advanced proximal gastric adenocarcinoma were selected from the National Cancer Data Base (2004–2015) in America. Survival analysis was performed via Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Among the included studies, the study conducted by Tang et al (2020) ( 25 ) accounted for 91.0% of the samples. The age of the subjects ranged from 57.03 to 64.46 years and 78.80% were male.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the included studies, the study conducted by Tang et al (2020) ( 25 ) accounted for 91.0% of the samples. The age of the subjects ranged from 57.03 to 64.46 years and 78.80% were male.…”
Section: Resultsmentioning
confidence: 99%
“…However, rather than reporting no long-term differences in survival, the study by Tang et al ( 25 ), which had the largest study population, showed an improved survival benefit in patients undergoing PG compared with that in patients undergoing TG. Patient characteristics were a factor in the study, as among all the patients, those in the TG group had a poorer prognosis than those in the PG group, and patients receiving post-operative chemotherapy had a somewhat better long-term survival rate than those receiving surgery alone.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the 5-year survival rate among Iranian patients diagnosed with GC has been recorded to be below 11%. [ 22 23 24 ] Many investigations have been conducted on the role of lncRNAs in cancer development and management. Detection of GC subtypes based on the determined molecular profile leads to more satisfied and substantial treatment approaches by personalized clinical recognition and identifying biomarkers for screening, prognostic, prompt diagnosis, and surveillance of cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer ranks fifth in terms of incidence and third in terms of mortality [ 3 , 4 ]. An estimated 1 million new gastric cancer cases were diagnosed and 0.78 million deaths occurred in 2018 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%